ANALISIS YURIDIS PELAKSANAAN PEMBEBANAN HAK TANGGUNGAN DALAM PERJANJIAN KREDIT BANK DI KOTA PONTIANAK - NIM. A1011191248, MUHAMMAD NABIL KAUTSAR PRIYANTANA (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractCredit has a very significant role today, because the business world is growing. Whether the trade, industry, agriculture, housing, services and others sectors, credit is a driving factor in that regard. With the credit provided by the bank, it must cause risk. Because not all debtors are good in practice. Therefore, that is what causes the need for guarantees in every provision of credit. Land rights are one type of guarantee. In Law Number 4 of 1996 concerning Dependent Rights along with objects related to land, it is determined that Property Rights, Building Use Rights, Business Use Rights can be used as debt security by being burdened with Dependent Rights. The purpose of this study is to discuss the implementation of credit agreements with guaranteed Rights of Dependents and the imposition of Rights of Dependents in credit agreements. The method used in this thesis research is a normative problem approach and is supported by field studies. The data source used is a secondary data source (legislation). Data collection method with literature study and interview. The implementation of the credit agreement is preceded by a credit application by the prospective debtor to the financial institution or bank. Then the financial institution analyzes the credit application file and the results are given to a notary. If there is a certificate that has not returned the name, it will not be accepted by the notary, and it is necessary to use a power of attorney. The legal consequences that will occur if the certificate has not been rebranded are bad debts, defaults and other legal consequences. The effort in that case is before applying for a dependent right, the new owner or debtor should consult with the competent authorities and also with the bank that will provide credit and the financial institution or bank needs to be more careful in analyzing the file. The imposition of dependent rights is preceded by the granting of dependent rights by making a Deed of Granting Dependent Rights (APHT) in PPAT. Then registration of dependent rights is carried out at the Land Office by making a land book of Dependent Rights. Proof of Right of Dependency the Land Office issues a certificate of right of dependents containing irah-irah with the words